2019
DOI: 10.4314/tjpr.v18i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vanillin in streptozotocin-induced diabetes in neonatal rats via attenuation of oxidative stress and inflammation

Abstract: Purpose: To evaluate the antidiabetic activity of vanillin in streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes was induced in 2-day old male pups by intraperitoneal (i.p.) administration of STZ (90 mg/kg). The pups were then randomly assigned to four groups: control group which received citrate buffer only in place of STZ; negative control group, i.e., diabetic group; and vanillin-treated groups which received vanillin (100 or 200 mg/kg, p.o.) continuously from the 6th week of age to the 10th week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The antioxidant and anticancer properties of vanillin are well-known, but this compound has also non negligible anti-hyperglycaemic effect. Lu et al [63] showed that this compound can regulate the serum level of glucose and insulin in diabetic rats and even conserve the integrity of pancreas tissues. Another study carried out by Iannuzzi et al [64] proved that this compound could prevent diabetes complications by blocking glycation of insulin, precisely via a non-covalent binding process between vanillin and positively charged arginine 22 (Arg22) of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and anticancer properties of vanillin are well-known, but this compound has also non negligible anti-hyperglycaemic effect. Lu et al [63] showed that this compound can regulate the serum level of glucose and insulin in diabetic rats and even conserve the integrity of pancreas tissues. Another study carried out by Iannuzzi et al [64] proved that this compound could prevent diabetes complications by blocking glycation of insulin, precisely via a non-covalent binding process between vanillin and positively charged arginine 22 (Arg22) of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It was reported in the literature that NGN and VLN significantly protected against streptozotocininduced pancreatic β-cell injury and diabetes mellitus. [14][15][16] In addition, NGN mitigated acute pancreatitis induced by caerulein and L-arginine in mice. 17 The current work was done to investigate the possible protective effects of NGN, VLN and NGN + VLN in a rat model of cadmium-induced pancreatic injury and to elucidate the feasible mechanisms mediating these protective effects.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to humans, in animal models of obesity, various dysfunctions are observed including raised body fat and triglyceride levels, glucose intolerance, and insulin resistance, which may lead (especially in extended exposure to HFD) to the development of T2D. A commonly used method to induce T2D in animals employs combination of feeding with HFD followed by injections of low doses of streptozotocin (a toxin that destroys the pancreas) 81 . Such animal models mimic the human condition, where T2D is often associated with obesity and a HFD.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used method to induce T2D in animals employs combination of feeding with HFD followed by injections of low doses of streptozotocin (a toxin that destroys the pancreas). 81 Such animal models mimic the human condition, where T2D is often associated with obesity and a HFD.…”
Section: Introductionmentioning
confidence: 99%